Exploring customer motivation and behavioural intention: a case study of Malaysian Chinese university students and their behavioural intentions on using xiaohongshu (red) - Bong, Dena Kah Huan (2024)

(untitled)
Social media has a significant influence on human life, and people will utilise it for different purposes to satisfy their needs. The rise of XiaoHongShu, commonly known as RED, has gained significant attention in Malaysian society due to its widespread usage among the population. This study aims to study the relationship between customer motivation and behavioural intention when using RED among Chinese students enrolled in Malaysia's universities with the application of Uses and Gratification Theory. A cross-sectional study involving 104 respondents was undertaken using the purposive sampling approach. The collected data were analysed using the SPSS software. The targeted respondents were Malaysian Chinese university students aged between 18 and 27 years old, with the majority falling within the 21 to 23 age range (n = 77, 74%). The instruments used were Information Seeking Scale, Relaxing Entertainment Scale, Social Interaction Scale, Purchase Intention Scale, and Engagement Scale. The finding of this study showed that there is a significant positive relationship between customer motivation and behavioural intention (r = 0.712). Information seeking motivation served as the primary factor in university students browsing RED, while purchase intention is a significant factor influencing behavioural intention. The findings would provide a practical insight for businesses and content creators to define marketing strategies by understanding customer motivations.